Tourisme et développement local : vers une redéfinition des relations au niveau de la Petite-Côte sénégalaise ? - Mamadou Diombera (Études Caribéennes, 2013)
This article puts the problem of the processes of tourist development at the level of the Senegalese Little-coast and their consequences on the sociocultural and economic background of the local populations. We observed an anarchy occupation of coastal environments, very desired for their tourist and economic interests, while they constitute fragile ecosystems, sensitive to the action of the anthropological agents. This is the way we made at first a current situation to see the stakes at the level of the planning and of the tourist development of the Little-coast. We analyzed then the consequences to propose strategies for a sustainable development by taking into account the peculiarities of the territory at the local, regional and national level in a globalized context. Besides, it is a question in this article of describing and deciphering the relationship, certainly, narrow but extremely feeder between tourism and local development by analyzing how the tourism impacts on the process of development and vice versa.